2019
DOI: 10.2147/imcrj.s170329
|View full text |Cite
|
Sign up to set email alerts
|

<p>Treatment of recurrent myopic macular hole using membrane of plasma rich in growth factors</p>

Abstract: Purpose To describe the case of a patient with a recurrent large myopic macular hole (MH), who was successfully treated with a plasma rich in growth factors (PRGF) membrane. Case Report A 71-year-old patient presented a myopic MH in his right eye. One month later, pars plana vitrectomy with internal limiting membrane (ILM) peeling was performed, achieving closure of the MH. Three months later a recurrence was observed (700 µm) without visual acuity (VA) improvement. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In addition, it is also involved in eye hydration [37] and reducing inflammation. Previous research has shown the retina responds well to PRGF treatment [38]. Therefore, the inherent features of PRGF suggest that it could act as an antioxidant agent.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it is also involved in eye hydration [37] and reducing inflammation. Previous research has shown the retina responds well to PRGF treatment [38]. Therefore, the inherent features of PRGF suggest that it could act as an antioxidant agent.…”
Section: Introductionmentioning
confidence: 98%
“…Since the 1990s, blood derivatives (autologous serum, autologous platelet concentrates (APC) or also called platelet rich plasma (PRP)) have been used classically as an adjuvant therapy to increase the rate of closure in MHs [ 14 , 34 ]. More recently, biological tissues have been used as scaffolding with the ability to release growth factors, including human amniotic membrane (hAM) [ 35 ], fibrin rich plasma [ 36 ], and PRGF [ 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRGF has demonstrated anti-inflammatory, anti-fibrotic, and regenerative functions in ocular surface and cornea diseases (dry eye, persistent epithelial defects, neurotrophic keratitis, among others) [ 19 , 20 , 21 , 22 ]. The use of the PRGF membrane in the closure of MH in high myopia has also achieved good anatomical and visual results [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In ophthalmology, it has been used for treating eye surface disorders such as PED or dry eye [ 25 , 27 , 28 , 29 , 31 , 47 , 49 ]. In terms of pathologies related to the retina, PRGF has also been used to treat macular holes, producing good results in both anatomical closure and vision recovery [ 32 , 33 ]. Other experimental studies demonstrated the neuroprotector role of PRGF in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in oral implantology and traumatology, and in ophthalmology for treating ocular surface diseases, such as persistent epithelial defects (PEDs) [ 25 , 26 , 27 , 28 , 29 ], conjunctivitis, or other ocular surface pathologies [ 30 , 31 ]. In the retina, PRGF has been proven to reduce macular holes [ 32 , 33 ]. Our group previously tested its effect on retinal pigment epithelium (RPE) through the reduction in the harm produced by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%